Does Anonymity Matter in Electronic Limit Order Markets? - Thierry Foucault; Sophie Moinas; Erik Theissen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Lecture on the first SFB/TR 15 meeting, Gummersbach, July, 18 - 20, 2004: We develop a model of limit order trading in which some traders have better information on future price volatility. As limit orders have option-like features, this information is valuable for limit order traders. We solve for informed and uninformed limit order traders' bidding strategies in equilibrium when limit order traders' IDs are concealed and when they are visible. In either design, a large (resp. small) spread signals that informed limit order traders expect volatility to be high (resp. low). However the quality of this signal and market liquidity are different in each market design. We test these predictions using a natural experiment. As of April 23, 2001, the limit order book for stocks listed on Euronext Paris became anonymous. For our sample stocks, we find that following this change, the average quoted and effective spreads declined significantly. Consistent with our model, we also find that the size of the spread is a predictor of future price volatility and that the strength of the association between the spread and volatility is weaker after the switch to anonymity.
urn:nbn:de:bvb:19-epub-13543-5
Keywords: G10; G14; G24; 330; Market Microstructure; Limit Order Trading; Anonymity; Transparency; Liquidity; Volatility Forecasts